Alcune note sulla ricezione anglosassone di Jacques Derrida (Rivista Italiana di Filosofia Analitica Junior, 2011)
The paper investigates some aspects of the relations between Derrida’s thought and the XX century american mainstream of thought in philosophy. In order to do this, it deepens the relevant perspective of deconstruction through frequent comparisons with crucial standpoint in history of philosophy, such as Aristotle, Descartes, Hegel, Heidegger.